Implementasi Sistem Jadwal Absensi Guru Dalam Peningkatan Kedisiplinan Pada SMAIT ASY - SYUKRIYYAH - Aris, Aris; Pangestu, Maulana Agung; Novianti, Rini (Universal Raharja Community (URNITY Journal), 2021)
Teacher absenteeism is one of the important points in measuring discipline in the world of education, especially in ASY-SYUKRIYYAH SMAIT. The recording of teacher absenteeism is recorded in the agenda which also includes the activities of the teacher related to the teaching and learning process in the classroom. The large number of absences and activities recorded manually raises problems in making attendance reports and teaching and learning in class. To overcome this problem required the design of information systems that can accommodate the recording of attendance and teaching and learning activities in the classroom. This research was conducted to produce an information system that can overcome problems that arise and be able to speed up the process of recording attendance, teaching and learning activities, and making reports. Information gathering uses the method of observation and literature study. Development of web-based systems and using PIECES and UML analysis as a system model. With this web-based information system can be a way out to facilitate related parties in supervising, checking and making reports related to the presence of teachers and the activity in the classroom more better, easily, effectively and efficiently.